(untitled) (Research, Society and Development, 2021)
Propolis is a natural substance that is produced by bees and has been used since ancient times for its pharmacological properties. The cattle tick Rhipicephalus (Boophilus) microplusis responsible for great economic losses by cattle breeding programs. The aim of the present study was to evaluate the in vitro effect of propolis extracts on engorged female ticks. The experiment was performed at the Uberaba IFTM. A completely randomized experimental design was used, including eight treatments and five replicates, with a total 40 experimental units, each consisting of 10 engorged females of homogeneous weight. The experimental units were immersed in alcoholic propolis extracts that were diluted with distilled water to the following concentrations: 0, 10, 20, 30, 40, 50, 60, and 70%. A regression analysis was used to analyze the relationship between propolis extract concentration and weight of eggs laid (WEL), hatching percentage (HP), and reproductive efficiency (RE). This demonstrates the viability of propolis as an alternative for the control of cattle ticks, with the 70% extract concentration being most efficientand most effective for controlling R. microplus under laboratory conditions.